Du « grand piétonnier » au projet urbain et métropolitain : atouts et défis pour le centre de Bruxelles (nouvelle édition) - Michel Hubert; Eric Corijn; Julie Neuwels; Margaux Hardy; Sofie Vermeulen; Joost Vaesen (Brussels Studies)
The new pedestrian area has been one of the main urban projects designed for the centre of Brussels in recent decades. In 2015, the transit route in the city centre - Boulevard Anspach - was closed to traffic. The redevelopment of public space and the renovation of the main metro stations are now nearing completion. The finalisation of this urban project and the challenges it has faced are, by definition, complex. Experiences elsewhere in the country and abroad, as well as the data collected by BSI-BCO, show that it will have a significant impact at different levels: quality of public space, housing and facilities, local economy and employment, mobility, accessibility and logistics, social and cultural activities, etc. This synopsis is an update of a previously published work (no. 115). Part 1 sets out the general context of this project which has not been spared by several external crises (lockdown following the attacks in Paris, attacks in Brussels, the tunnel crisis and, of course, the covid crisis). Part 2 develops the challenges which remain. In conclusion, this synopsis proposes some concrete ways to improve the quality and management of the project.